Emergency medicine, quick glance (McGraw-Hill, 2006)
This resource is a must for residents, students, physician assistants, and nurses working in the emergency department. With its carry-anywhere book/PDA format, Emergency Medicine Quick Glance puts the field's latest perspectives where you need them most: at the point of care. Concise yet comprehensive, this handy, at-a-glance resource is ideal for use in daily clinical practice or for a quick review.